Contextualization of Islamic Economic Principles of the Imam Khomeini - Hendri Hermawan Adinugraha; Ahmad Zayadi (Al-Buhuts, 2020)
In some decade this latter world economy much discuss the emergence of the concept of Islamic economics. This is because the conventional economic system which is more precisely known as the capitalist economic system causes injustice in the economy so that the rich get richer and the poor get poorer. Islamic economics is an alternative economic system and a new solution in the midst of economic inequality that hit countries in the world, especially countries with Muslim populations, including Indonesia. One of the figures who introduced Islamic economics was Imam Khomeini who was the founder of the Islamic Republic of Iran. According to him, Islamic economy has several principles that are different from the principles of socialist and capitalist economics. In other words, Islamic economics is a middle way between the socialist and capitalist economic system.